2022
DOI: 10.3390/ijms231911566
|View full text |Cite
|
Sign up to set email alerts
|

Archaea Microbiome Dysregulated Genes and Pathways as Molecular Targets for Lung Adenocarcinoma and Squamous Cell Carcinoma

Abstract: The human microbiome is a vast collection of microbial species that exist throughout the human body and regulate various bodily functions and phenomena. Of the microbial species that exist in the human microbiome, those within the archaea domain have not been characterized to the extent of those in more common domains, despite their potential for unique metabolic interaction with host cells. Research has correlated tumoral presence of bacterial microbial species to the development and progression of lung cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Pathoscope2 can identify strains, compute abundance levels, perform re-assignments, and output informative result summaries. It has seen usage in numerous studies [ 22 25 ], and its algorithm has also been incorporated into other taxonomic classification pipelines [ 16 ]. Kraken2 and Clark are two taxonomic classifiers that classify reads by assigning them a taxonomic ID.…”
Section: Resultsmentioning
confidence: 99%
“…Pathoscope2 can identify strains, compute abundance levels, perform re-assignments, and output informative result summaries. It has seen usage in numerous studies [ 22 25 ], and its algorithm has also been incorporated into other taxonomic classification pipelines [ 16 ]. Kraken2 and Clark are two taxonomic classifiers that classify reads by assigning them a taxonomic ID.…”
Section: Resultsmentioning
confidence: 99%
“…Pathoscope2 can identify strains, compute abundance levels, perform re-assignments, and output informative result summaries. It has seen usage in numerous studies [32,9,13,26] and its algorithm has also been incorporated into other taxonomic classification pipelines [8]. Kraken2 and Clark are two taxonomic classifiers that classify reads by assigning them a taxonomic ID.…”
Section: Resultsmentioning
confidence: 99%
“…So far, studies of the archaeome in cancer have been limited to colorectal cancer [ 56 , 57 ]. Thus, our investigation of the archaeometry in lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) was the first to associate archaeal microbes with pertinent metabolic and oncogenic pathways in any non-colorectal cancer [ 58 ]. In this paper, we found that intratumor archaeal species were distinctly dysregulated between LUAD and LUSC samples and exhibited associations with unique cellular pathway regulation and clinical progression variables.…”
Section: Discussionmentioning
confidence: 99%